2022
DOI: 10.1111/nmo.14524
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing multiple concurrent functional gastrointestinal disorders is associated with greater symptom severity and worse quality of life in chronic constipation and defecation disorders

Abstract: Background Recent community‐based studies have demonstrated that experiencing multiple concurrent functional gastrointestinal disorders (FGIDs) is associated with increased somatization, worse quality of life (QoL), and greater health care utilization. However, the presence of multiple overlapping FGIDs is unstudied specifically in chronic constipation and functional defecation disorders (FDD). We investigated the prevalence and impact of additional nonconstipation FGIDs on constipation severity, anorectal phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…As the number of rTMS sessions increases, these neural adaptations accumulate, potentially leading to more significant and sustained therapeutic effects (64). Studies have shown that patients with constipation are often accompanied by psychiatric symptoms such as anxiety and depression (30). In this The CSS, SAS, SDS, and SSS scale scores before rTMS treatment in the FBD treatment group with different sessions of rTMS.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As the number of rTMS sessions increases, these neural adaptations accumulate, potentially leading to more significant and sustained therapeutic effects (64). Studies have shown that patients with constipation are often accompanied by psychiatric symptoms such as anxiety and depression (30). In this The CSS, SAS, SDS, and SSS scale scores before rTMS treatment in the FBD treatment group with different sessions of rTMS.…”
Section: Discussionmentioning
confidence: 94%
“…The CSS (30) is a constipation score developed by the Cleveland Clinic. There are 8 self-test questions, with a full score of 30 points, and a minimum of 0 points.…”
Section: Treatment Sessions Rangementioning
confidence: 99%
“…The clinical features of the pediatric population in this region warrant specific investigation, with a higher prevalence of childhood constipation in South America than in other countries [ 22 ], accounting for one-third of pediatric gastroenterology consultations in Chile [ 23 ]. Disease overlap between IBS and functional defecation disorders is common and has been associated with increased symptom severity and decreased quality of life [ 24 ]. In the present study, the majority of participants had other DGBI including two-thirds with functional constipation, in addition to moderate or severe IBS at baseline, yet the probiotic proved to be highly effective.…”
Section: Discussionmentioning
confidence: 99%
“…Just as an increasing burden of all medical diagnoses has been show to impact QoL negatively in all individuals, QoL is likewise negatively impacted when there is a diagnosis of multiple DGBIs in a patient (Kaplan et al, 2023; Sperber et al, 2022). However, our study did not have a large enough sample size to make such conclusions in the DS population with multiple DGBI diagnoses.…”
Section: Discussionmentioning
confidence: 99%